Atlantoaxial Rotatory Fixation after Ventriculoperitoneal Shunting - Heary, R. F.; Reid, P.; Carmel, P. W. (Neuropediatrics, 2011)
Ventriculoperitoneal (VP) shunting is a common neurosurgical procedure in the pediatric population. Atlantoaxial rotatory fixation (AARF) is not uncommon in this same group. We present the first reported case of AARF following a VP shunt procedure. A 10-year-old boy, with hydrocephalus and a left temporal arachnoid cyst since birth, underwent a revision of his VP and cystoperitoneal shunts. A second operation was performed 2 days later to optimize catheter placement. Postoperative neck pain was attributed to tunneling of the subcutaneous catheter. 2 months after surgery, the child had minimal neck discomfort but maintained his head in a “cock-robin” position. Plain radiographs and computed tomographic (CT) images confirmed AARF. The child was admitted and placed in halo traction. After 3 days of traction, analgesics, sedation, and muscle relaxants, anatomic re-alignment of the C1-C2 vertebral complex was confirmed on CT scan. Following 3 months of immobilization in a halo-vest apparatus, the halo was removed. At 8-year follow-up, the clinical examination is normal and repeat imaging studies remain normal. Due to surgical positioning, and postoperative signs attributed to normal postoperative pain, an AARF was not initially recognized. This case represents the first time that AARF has been reported following a VP shunt procedure.
Keywords: atlantoaxial rotatory fixation; traction; ventriculoperitoneal shunt; halo